(untitled) - Morelli, R. (Ralph) (Upper Saddle River, N.J., 2000)
The text uses a top-down approach to focus on problem decomposition and program design from the beginning. It is this methodology-along with its lucid and engaging exercises and analogies- that sets this book apart. Morelli introduces some of Javas advanced features including GUIs (e.g. AWT and Swing), exceptions, threads, files, and sockets. Because of this resources adaptable and accessible style, instructors can easily choose which advanced concepts to teach to introductory students while intermediate level programmers can also benefit from its thorough advanced feature coverage.
Keywords: Java (Computer program language),Java (Ngôn ngữ chương trình máy tính)